A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x Preparation and bifunctional application of S
By loading sulfide nano-nano-containing nano-nano-containing nano-sulfur nanosius in the surface of the cobalt-based amporotic skeleton, the BI2S3-Δ/CO1-XS composite material is constructed, and the problem of the metal sulfide photoelectric catalyst is easily corroded and rapidly compounded by the electronic plane. Efficient photovoltaic catalysis decomposes hydrogen and organic pollutants degradation.
Patent Information
- Application Number
- CN202310994105.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-08-09
AI Technical Summary
Existing metal sulfide photoelectric catalysts are susceptible to photocorrosion, and the rapid recombination of electron holes limits the efficiency of photocatalytic decomposition of water to produce hydrogen.
Through the combination of solvent thermal method, the surface of the sulfur-containing gap containing vulcanic nanoprobus containing a sulfur gap on the surface of the cobalt-based amporogy is built, and the BI2S3-Δ/CO1-XS composite material with Yin and cations is built.
It significantly improves the performance of photovoltaic catalysis to decompose water and hydrogen producing hydrogen -producing the ability to degrade organic pollutants, and has low cost and good light absorption.
Smart Images

Figure CN117123239B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrocatalytic decomposition of water to produce hydrogen, and in particular to a photoelectrocatalyst Bi2S having sulfur / cobalt anion and cation double vacancies. 3-δ / Co 1-x Preparation and bifunctional applications of S. Background Art
[0002] Metal sulfides are susceptible to photocorrosion and are difficult to maintain long-term stability. At the same time, the rapid recombination of electrons and holes limits the development and application of photocatalytic water decomposition to produce hydrogen to a certain extent. Bismuth sulfide has a direct narrow band gap of 1.3-1.7 eV, which gives it a good visible light response and has broad application prospects in solar hydrogen production. x S y Transition metal sulfides have great potential in the field of photocatalysis. They have the advantages of excellent conductivity, structural adjustability, large specific surface area, and abundant active sites obtained by multiple reflections of light in the hollow structure of the cobalt-based zeolite imidazolate framework to improve photocatalytic activity.
[0003] Defect engineering is one of the strategies to improve the photoelectrocatalytic performance of metal sulfides. The presence of defects can regulate the energy band position of semiconductor materials to extend the light absorption range. At the same time, certain defects can provide more catalytic active sites and have an important impact on the separation and transfer of charges, thereby improving the efficiency of the entire photoelectrocatalytic reaction process. Among them, vacancy regulation is an important part of defect engineering. When anion and cation vacancies coexist in the photocatalyst, anion vacancies can serve as electron capture centers, and cation vacancies can serve as capture centers for photogenerated holes, which can significantly improve the transfer and separation of photogenerated carriers, thereby improving photocatalytic activity.
[0004] Therefore, we designed to introduce sulfur vacancies into bismuth sulfide to improve its energy band and electronic structure, and then in situ constructed an S-type heterojunction composite photocatalyst Bi2S with anion and cation double vacancies through a precipitation method with hollow cobalt sulfide. 3-δ / Co 1-x So far, the anion and cation divacancy in Bi2S 3-δ With Co 1-x There is no public report on the construction of S-type heterojunction photoelectric catalysts. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems existing in the prior art and provide a photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies. 3-δ / Co 1-x Preparation and bifunctional applications of S.
[0006] To achieve the above purpose, the technical solution provided by the present invention is: a photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x The preparation of S comprises firstly loading bismuth sulfide nanorods containing sulfur vacancies on the surface of a cobalt-based zeolite imidazole ester framework by a solvothermal method combined with a precipitation method to obtain a cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies, and then sulfiding the cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies to construct a hollow polyhedral structure of Bi2S containing anion and cation double vacancies. 3-δ / Co 1-x S composite material; the specific preparation process is:
[0007] (1) Weighing a certain amount of bismuth nitrate pentahydrate and adding it to a certain volume of ethylene glycol, ultrasonicating for a certain time until the reagent is fully dissolved to obtain solution 1; weighing a certain amount of thiourea and adding it to a certain volume of ethylene glycol, stirring until the reagent is fully dissolved to obtain solution 2; then slowly dropping solution 2 into solution 1, placing it at room temperature and magnetically stirring it for a certain time, transferring it to a reactor, rapidly heating it to a certain temperature and keeping it warm for a certain time; after the reaction is completed and the device is cooled, centrifuging it to obtain a precipitate, then washing the precipitate several times, then placing the washed precipitate in a vacuum drying oven to dry for a certain time, and finally grinding it to obtain Bi2S 3-δ ;
[0008] (2) Take a certain amount of cobalt nitrate hexahydrate and fully dissolve it in a certain volume of methanol, then add a certain amount of Bi2S 3-δ , and fully stirred until completely dispersed to obtain solution 3; weigh a certain amount of 2-methylimidazole and add it to a certain volume of methanol, stir until completely dissolved to obtain solution 4, then quickly drop solution 4 into solution 3, vigorously stir for a certain time, then place it at room temperature for aging for a certain time, centrifuge to obtain a precipitate, then wash the precipitate several times, then place the washed precipitate in a vacuum drying oven for a certain time, and finally grind to obtain Bi2S 3-δ / ZIF-67 precursor;
[0009] (3) Weigh a certain amount of Bi2S from step (2) 3-δ / ZIF-67 precursor and a certain amount of thioacetamide are placed in a certain volume of anhydrous ethanol, stirred vigorously for a period of time until the mixture is uniform, and then transferred to a reactor, reacted at a certain temperature for a certain time, after the reaction is completed and cooled to room temperature, centrifuged to obtain a precipitate, and then washed several times, and then the washed precipitate is placed in a vacuum drying oven for a certain period of time, and finally ground and dried to obtain a powder product, which is Bi2S 3-δ / Co 1-x S composite material.
[0010] Preferably, in step (1), the amount of bismuth nitrate pentahydrate added is 1-8 mmol, the amount of thiourea added is 2-15 mmol, the volume of ethylene glycol is 10-80 ml, the time for ultrasonic dispersion of bismuth nitrate pentahydrate added to ethylene glycol is 10-60 min, the time for magnetic stirring at room temperature is 30-90 min, the heating temperature in the reactor is 50-250 ° C, and the insulation time is 2-10 h.
[0011] Preferably, in step (2), the amount of cobalt nitrate hexahydrate added is 0.5-8 mmol, Bi2S 3-δ The amount of Bi2S added is 25-200 mg, the amount of 2-methylimidazole added is 5-50 mmol, the volume of methanol is 10-80 ml, 3-δ / ZIF-67 precursor, Bi2S 3-δ The mass ratio of solution 4 to ZIF-67 precursor is 0.5-0.9:1.1-2.5; the vigorous stirring time of dropping solution 4 into solution 3 is 5-40 minutes, and the aging time is 20-80 minutes.
[0012] Preferably, in step (3), thioacetamide and Bi2S 3-δ The mass ratio of / ZIF-67 precursor is 0.9-1.8:0.8-1.7, the volume of anhydrous ethanol is 20-60 ml, the vigorous stirring time is 5-30 min, the heating temperature of the reactor is 100-240° C., and the insulation time is 5-12 h.
[0013] Preferably, the vacuum drying oven drying temperature in step (1), step (2) and step (3) is 30-150°C, and the insulation time is 6-16h; the centrifugal speed is 5000-12000r / min, and the time is set to 1-6min.
[0014] The present invention also discloses a photoelectric catalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x The dual-function application of S can be realized by using Bi2S under visible light irradiation and a small external bias. 3-δ / Co 1-x S composite photoelectrocatalyst realizes the dual-functional application of catalytic hydrogen production and simultaneous degradation of organic pollutants.
[0015] Beneficial effects of the present invention:
[0016] The present invention adopts a solvent thermal method combined with a precipitation method to prepare Bi2S 3-δ and Co 1-x S to construct anion vacancies (V S ) and cation vacancies (V Co), providing more active sites for the catalytic reaction, and the vacancies also become the recombination centers of invalid photogenerated charges, accelerating the separation of carriers and thus improving the hydrogen production performance.
[0017] The photoelectric catalyst Bi2S with sulfur / cobalt anion and cation double vacancies of the present invention 3-δ / Co 1-x S and pure substances (Bi2S3, Bi2S 3-δ 、Co 1-x S) and the composite containing a single cobalt vacancy (Bi2S3 / Co 1-x S) catalysts were used to compare the hydrogen production performance, divacancy Bi2S 3-δ / Co 1-x The photoelectrocatalytic hydrogen production from water by S-complex catalyst is significantly better than that of pure substances and single cobalt vacancy Bi2S3 / Co 1-x The performance of S catalyst was excellent, and it showed excellent ability of hydrogen production and simultaneous degradation of organic pollutants.
[0018] Therefore, the photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies prepared in the present invention 3-δ / Co 1-x S not only has the advantages of low cost, good light absorption performance and excellent photoelectric performance, but also has a certain ability to produce hydrogen and degrade organic pollutants simultaneously. In the dual-function application of photoelectrocatalytic decomposition of water to produce hydrogen and degrade organic pollutants simultaneously, applying a small external bias can significantly increase the rate of hydrogen production from photoelectrocatalytic decomposition of water on the basis of greatly enhancing the absorption range and intensity of visible light, which is of great significance to the development of green hydrogen energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 The Bi2S prepared in the present invention 3-δ / Co 1-x Schematic diagram of the synthesis process of S sample;
[0021] Figure 2 The Bi2S3 and Bi2S prepared by the present invention 3-δ 、Co 1-x S, Bi2S 3-δ / Co 1-x XRD pattern of S composite photocatalyst sample;
[0022] Figure 3 The Bi2S prepared in the present invention 3-δ / Co 1-xTransmission image of S sample;
[0023] Figure 4 The simple hydrogen production rate (a) and the synergistic hydrogen production (b) of the sample obtained by the present invention by simultaneous degradation of methyl orange (MO) are shown. DETAILED DESCRIPTION
[0024] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.
[0025] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0026] In the description of the present invention, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed" etc. are understood as not including the number itself, and "above", "below", "within" etc. are understood as including the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0027] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0028] Reference Figure 1-Figure 4 , a preferred embodiment of the present invention, a photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x The preparation method of S is characterized in that: firstly, by a solvothermal method combined with a precipitation method, bismuth sulfide nanorods containing sulfur vacancies are loaded on the surface of a cobalt-based zeolite imidazole ester framework to obtain a cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies, and then the cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies is sulfurized to construct a hollow polyhedral structure of Bi2S containing anion and cation double vacancies. 3-δ / Co 1-x S composite material; the specific preparation process is:
[0029] (1) Weighing a certain amount of bismuth nitrate pentahydrate and adding it to a certain volume of ethylene glycol, ultrasonicating for a certain time until the reagent is fully dissolved to obtain solution 1; weighing a certain amount of thiourea and adding it to a certain volume of ethylene glycol, stirring until the reagent is fully dissolved to obtain solution 2; then slowly dropping solution 2 into solution 1, placing it at room temperature and magnetically stirring it for a certain time, transferring it to a reactor, rapidly heating it to a certain temperature and keeping it warm for a certain time; after the reaction is completed and the device is cooled, centrifuging it to obtain a precipitate, then washing the precipitate several times, then placing the washed precipitate in a vacuum drying oven to dry for a certain time, and finally grinding it to obtain Bi2S 3-δ ;
[0030] (2) Take a certain amount of cobalt nitrate hexahydrate and fully dissolve it in a certain volume of methanol, then add a certain amount of Bi2S 3-δ , and fully stirred until completely dispersed to obtain solution 3; weigh a certain amount of 2-methylimidazole and add it to a certain volume of methanol, stir until completely dissolved to obtain solution 4, then quickly drop solution 4 into solution 3, vigorously stir for a certain time, then place it at room temperature for aging for a certain time, centrifuge to obtain a precipitate, then wash the precipitate several times, then place the washed precipitate in a vacuum drying oven for a certain time, and finally grind to obtain Bi2S 3-δ / ZIF-67 precursor;
[0031] (3) Weigh a certain amount of Bi2S from step (2) 3-δ / ZIF-67 precursor and a certain amount of thioacetamide are placed in a certain volume of anhydrous ethanol, stirred vigorously for a period of time until the mixture is uniform, and then transferred to a reactor, reacted at a certain temperature for a certain time, after the reaction is completed and cooled to room temperature, centrifuged to obtain a precipitate, and then washed several times, and then the washed precipitate is placed in a vacuum drying oven for a certain period of time, and finally ground and dried to obtain a powder product, which is Bi2S 3-δ / Co 1-x S composite material.
[0032] In this embodiment, in step (1), the amount of bismuth nitrate pentahydrate added is 1-8 mmol, the amount of thiourea added is 2-15 mmol, the volume of ethylene glycol is 10-80 ml, the time for ultrasonic dispersion of bismuth nitrate pentahydrate added to ethylene glycol is 10-60 min, the time for magnetic stirring at room temperature is 30-90 min, the heating temperature in the reactor is 50-250° C., and the insulation time is 2-10 h.
[0033] In this embodiment, in step (2), the amount of cobalt nitrate hexahydrate added is 0.5-8 mmol, Bi2S 3-δThe amount of Bi2S added is 25-200 mg, the amount of 2-methylimidazole added is 5-50 mmol, the volume of methanol is 10-80 ml, 3-δ / ZIF-67 precursor, Bi2S 3-δ The mass ratio of solution 4 to ZIF-67 precursor is 0.5-0.9:1.1-2.5; the vigorous stirring time of dropping solution 4 into solution 3 is 5-40 minutes, and the aging time is 20-80 minutes.
[0034] In this embodiment, in step (3), thioacetamide and Bi2S 3-δ The mass ratio of / ZIF-67 precursor is 0.9-1.8:0.8-1.7, the volume of anhydrous ethanol is 20-60 ml, the vigorous stirring time is 5-30 min, the heating temperature of the reactor is 100-240° C., and the insulation time is 5-12 h.
[0035] In this embodiment, the vacuum drying oven drying temperature in step (1), step (2) and step (3) is 30-150°C, and the insulation time is 6-16h; the centrifugal speed is 5000-12000r / min, and the time is set to 1-6min.
[0036] The present invention also discloses a photoelectric catalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x The dual-function application of S can be realized by using Bi2S under visible light irradiation and a small external bias. 3-δ / Co 1-x S composite photoelectrocatalyst realizes the dual-functional application of catalytic hydrogen production and simultaneous degradation of organic pollutants.
[0037] Example 1
[0038] (1) 1 mmol of bismuth nitrate pentahydrate was added to 10 ml of ethylene glycol and ultrasonicated for 20 min until fully dissolved to obtain solution 1; similarly, 2 mmol of thiourea was added to 10 ml of ethylene glycol and stirred until the reagent was fully dissolved to obtain solution 2, and then solution 2 was slowly added dropwise to solution 1, and the mixed solution was placed at room temperature and magnetically stirred for 30 min, then transferred to a 50 ml reactor, quickly heated to 160°C and kept warm for 3 h. After the sample was cooled to room temperature, the precipitate obtained by centrifugation was washed several times with deionized water and anhydrous ethanol, and finally the obtained product was placed at 60°C and vacuum dried for 12 h. The sample collected was Bi2S 3-δ ;
[0039] (2) Add 0.65 mmol of cobalt nitrate hexahydrate to 10 ml of methanol, and then add 25 mg of the Bi2S 3-δIn it, stir thoroughly until completely dispersed to obtain solution 3. Similarly, 5.2 mmol of 2-methylimidazole was added to 10 ml of methanol and stirred until completely dissolved to obtain solution 4, then solution 4 was quickly dropped into solution 3, stirred vigorously for 10 min, and then aged at room temperature for 20 min, and then the precipitate was washed several times with anhydrous ethanol, placed in a vacuum drying oven, dried at 60 ° C for 12 h, and then ground and collected. The dried product is Bi2S 3-δ / ZIF-67;
[0040] (3) Weigh 80 mg of the Bi2S 3-δ / ZIF-67 and 80 mg of thioacetamide were placed in 27 ml of anhydrous ethanol and stirred vigorously for 10 min, then transferred to a 50 ml reactor and kept at 150 °C for 8 h. After the device was cooled to room temperature, the precipitate obtained by centrifugation was washed several times with deionized water and anhydrous ethanol, and finally the obtained product was placed at 60 °C and vacuum dried for 12 h to obtain Bi2S 3-δ / Co 1-x S.
[0041] Example 2
[0042] (1) Add 2 mmol of bismuth nitrate pentahydrate to 20 ml of ethylene glycol and ultrasonicate for 30 min until fully dissolved to obtain solution 1; similarly, add 4 mmol of thiourea to 20 ml of ethylene glycol and stir until the reagent is fully dissolved to obtain solution 2, then slowly add solution 2 dropwise to solution 1, and then place the mixed solution at room temperature and magnetically stir for 40 min, then transfer to a 100 ml reactor, quickly heat to 180°C and keep warm for 4 h. After the sample is cooled to room temperature, the precipitate obtained by centrifugation is washed several times with deionized water and anhydrous ethanol, and finally the obtained product is placed at 80°C and vacuum dried for 10 h, and finally the obtained sample is collected and named Bi2S 3-δ .
[0043] (2) Add 2.44 mmol of cobalt nitrate hexahydrate to 20 ml of methanol, and then add 50 mg of the Bi2S 3-δ In it, stir thoroughly until completely dispersed to obtain solution 3. Similarly, 19.5 mmol of 2-methylimidazole was added to 20 ml of methanol and stirred until completely dissolved to obtain solution 4, and then solution 4 was quickly dropped into solution 3, stirred vigorously for 20 min, and then aged at room temperature for 30 min, and then the precipitate was washed several times with anhydrous ethanol, placed in a vacuum drying oven, dried at 80 ° C for 10 h, and then ground and collected to obtain Bi2S 3-δ / ZIF-67;
[0044] (3) Weigh 100 mg of the Bi2S3-δ / ZIF-67 and 120 mg of thioacetamide were placed in 54 ml of anhydrous ethanol and stirred vigorously for 15 min, then transferred to a 100 ml reactor and kept at 160 °C for 6 h. After the device was cooled to room temperature, the precipitate obtained by centrifugation was washed several times with deionized water and anhydrous ethanol, and finally the obtained product was placed at 80 °C and vacuum dried for 10 h to obtain Bi2S 3-δ / Co 1-x S.
[0045] Example 3
[0046] (1) 4 mmol of bismuth nitrate pentahydrate was added to 40 ml of ethylene glycol and ultrasonicated for 40 min until fully dissolved to obtain solution 1; similarly, 8 mmol of thiourea was added to 40 ml of ethylene glycol and stirred until the reagent was fully dissolved to obtain solution 2, then solution 2 was slowly added dropwise to solution 1, and the mixed solution was placed at room temperature and magnetically stirred for 60 min, then transferred to a 100 ml reactor and quickly heated to 200°C and kept warm for 5 h. After the sample was cooled to room temperature, the precipitate obtained by centrifugation was washed several times with deionized water and anhydrous ethanol, and finally the obtained product was placed at 90°C and vacuum dried for 8 h, and finally the obtained sample was collected and named Bi2S 3-δ ;
[0047] (2) Add 5.9 mmol of cobalt nitrate hexahydrate to 40 ml of methanol, and then add 75 mg of the Bi2S 3-δ and stirred thoroughly until completely dispersed to obtain solution 3. Similarly, 47.2 mmol of 2-methylimidazole was added to 40 ml of methanol and stirred until completely dissolved to obtain solution 4, and then solution 4 was quickly dropped into solution 3 and stirred vigorously for 30 min, and then aged at room temperature for 40 min, and then the precipitate was washed several times with anhydrous ethanol, and placed in a vacuum drying oven at 90 ° C for 8 h, and then the dried product was collected by grinding;
[0048] (3) Weigh 100 mg of the Bi2S 3-δ / ZIF-67 and 90 mg of thioacetamide were placed in 40 ml of anhydrous ethanol and stirred vigorously for 20 min, then transferred to a 100 ml reactor and kept at 160 °C for 6 h. After the device was cooled to room temperature, the precipitate obtained by centrifugation was washed several times with deionized water and anhydrous ethanol, and finally the obtained product was placed at 90 °C and vacuum dried for 8 h to obtain Bi2S 3-δ / Co 1-x S.
[0049] Example 4
[0050] (1) First, carbon paper (1×1.5 cm) was treated with anhydrous ethanol, 18 mol / L H2SO4, 0.1 mol / L H2SO4, and deionized water in sequence. 2 ) was ultrasonically cleaned for 15 min. 4 mg of divacancy Bi2S 3-δ / Co 1-x The S composite photoelectrocatalytic material was uniformly dispersed in 1 ml of a mixed solution of isopropanol and deionized water, and then uniformly coated on the surface of the treated carbon sheet (effective area 1×1 cm 2 , the rest was encapsulated with 5wt% Nafion) to obtain divacancy Bi2S 3-δ / Co 1-x S composite photoelectrocatalytic material electrode sheet.
[0051] (2) The dual-function performance test of photoelectrocatalytic water decomposition to produce hydrogen and simultaneously degrade organic pollutants was carried out. The electrolyte was a mixed solution of 78 ml of potassium hydroxide (1 mol / L) and 12 ml of methyl orange (15 mg / L). The electrode sheet described in step (1) was used as the working electrode, and the saturated calomel electrode and platinum sheet were used as the reference electrode and the counter electrode, respectively. Under a bias voltage of -0.4 V (relative to the standard hydrogen electrode), a 300 W xenon lamp was used as the light source, and the concentration of methyl orange at different time periods was determined by high performance liquid chromatography, and the amount of hydrogen produced was determined every half an hour by gas chromatograph.
[0052] Bis(II) vacancy photoelectrocatalytic material prepared by the patented technology of this invention 3-δ / Co 1-x S, whose hydrogen production rate for catalytic water decomposition under visible light is Bi2S3 / Co2S3, Bi2S3 / Co ... 1-x The amount of hydrogen released by hydrogen production and simultaneous degradation of organic pollutants is 2-5 times higher than that of hydrogen production alone.
[0053] The present invention adopts a solvent thermal method combined with a precipitation method to prepare Bi2S 3-δ and Co 1-x S to construct anion vacancies (V S ) and cation vacancies (V Co ), providing more active sites for the catalytic reaction, and the vacancies also become the recombination centers of invalid photogenerated charges, accelerating the separation of carriers and thus improving the hydrogen production performance.
[0054] The photoelectric catalyst Bi2S with sulfur / cobalt anion and cation double vacancies of the present invention 3-δ / Co 1-x S and pure substances (Bi2S3, Bi2S 3-δ 、Co 1-x S) and the composite containing a single cobalt vacancy (Bi2S3 / Co1-x S) catalysts were used to compare the hydrogen production performance, divacancy Bi2S 3-δ / Co 1-x The photoelectrocatalytic hydrogen production from water by S-complex catalyst is significantly better than that of pure substances and single cobalt vacancy Bi2S3 / Co 1-x The performance of S catalyst was excellent, and it showed excellent ability of hydrogen production and simultaneous degradation of organic pollutants.
[0055] Therefore, the photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies prepared in the present invention 3-δ / Co 1-x S not only has the advantages of low cost, good light absorption performance and excellent photoelectric performance, but also has a certain ability to produce hydrogen and degrade organic pollutants simultaneously. In the dual-function application of photoelectrocatalytic decomposition of water to produce hydrogen and degrade organic pollutants simultaneously, applying a small external bias can significantly increase the rate of hydrogen production from photoelectrocatalytic decomposition of water on the basis of greatly enhancing the absorption range and intensity of visible light, which is of great significance to the development of green hydrogen energy.
[0056] The invention has a simple process, low requirements on equipment, low pollution, and a wide range of sunlight utilization. The introduced sulfur vacancies and cobalt vacancies can significantly improve the separation ability of photogenerated charges, and is expected to be applied to efficient solar photoelectric catalytic decomposition of water to produce hydrogen and simultaneously degrade organic pollutants.
[0057] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.
[0058] The above description is only a preferred implementation mode of the present invention. Any technical solution that achieves the purpose of the present invention by substantially the same means belongs to the protection scope of the present invention.
Claims
1. A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies 3-δ / Co 1-x The preparation method of S is characterized by: Firstly, bismuth sulfide nanorods containing sulfur vacancies were loaded on the surface of the cobalt-based zeolite imidazole ester framework by a solvothermal method combined with a precipitation method to obtain a cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies. Then, the cobalt-based zeolite imidazole framework precursor containing bismuth sulfide with sulfur vacancies was sulfurized to construct a hollow polyhedral structure of Bi2S containing anion and cation double vacancies. 3-δ / Co 1-x S composite material; the specific preparation process is: (1) Weighing a certain amount of bismuth nitrate pentahydrate and adding it to a certain volume of ethylene glycol, ultrasonicating for a certain time until the reagent is fully dissolved to obtain solution 1; weighing a certain amount of thiourea and adding it to a certain volume of ethylene glycol, stirring until the reagent is fully dissolved to obtain solution 2; then slowly dropping solution 2 into solution 1, placing it at room temperature and magnetically stirring it for a certain time, transferring it to a reactor, rapidly heating it to a certain temperature and keeping it warm for a certain time; after the reaction is completed and the device is cooled, centrifuging it to obtain a precipitate, then washing the precipitate several times, then placing the washed precipitate in a vacuum drying oven to dry for a certain time, and finally grinding it to obtain Bi2S 3-δ ; (2) Take a certain amount of cobalt nitrate hexahydrate and fully dissolve it in a certain volume of methanol, then add a certain amount of Bi2S 3-δ , and fully stirred until completely dispersed to obtain solution 3; weigh a certain amount of 2-methylimidazole and add it to a certain volume of methanol, stir until completely dissolved to obtain solution 4, then quickly drop solution 4 into solution 3, vigorously stir for a certain time, then place it at room temperature for aging for a certain time, centrifuge to obtain a precipitate, then wash the precipitate several times, then place the washed precipitate in a vacuum drying oven for a certain time, and finally grind to obtain Bi2S 3-δ / ZIF-67 precursor; (3) Weigh a certain amount of Bi2S from step (2) 3-δ / ZIF-67 precursor and a certain amount of thioacetamide are placed in a certain volume of anhydrous ethanol, stirred vigorously for a period of time until the mixture is uniform, and then transferred to a reactor, reacted at a certain temperature for a certain time, after the reaction is completed and cooled to room temperature, centrifuged to obtain a precipitate, and then washed several times, and then the washed precipitate is placed in a vacuum drying oven for a certain period of time, and finally ground and dried to obtain a powder product, which is Bi2S 3-δ / Co 1-x S composite material.
2. A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies according to claim 1 3-δ / Co 1-x The preparation method of S is characterized by: In step (1), the amount of bismuth nitrate pentahydrate added is 1-8 mmol, the amount of thiourea added is 2-15 mmol, the volume of ethylene glycol is 10-80 ml, the time for ultrasonic dispersion of bismuth nitrate pentahydrate added to ethylene glycol is 10-60 min, the time for magnetic stirring at room temperature is 30-90 min, the heating temperature in the reactor is 50-250° C., and the insulation time is 2-10 h.
3. A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies according to claim 1 3-δ / Co 1-x The preparation method of S is characterized by: In step (2), the amount of cobalt nitrate hexahydrate added is 0.5-8 mmol, Bi2S 3-δ The amount of Bi2S added is 25-200 mg, the amount of 2-methylimidazole added is 5-50 mmol, the volume of methanol is 10-80 ml, 3-δ / ZIF-67 precursor, Bi2S 3-δ The mass ratio of solution 4 to ZIF-67 precursor is 0.5-0.9:1.1-2.5; the vigorous stirring time of dropping solution 4 into solution 3 is 5-40 minutes, and the aging time is 20-80 minutes.
4. A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies according to claim 1 3-δ / Co 1-x The preparation method of S is characterized by: In step (3), thioacetamide and Bi2S 3-δ The mass ratio of / ZIF-67 precursor is 0.9-1.8:0.8-1.7, the volume of anhydrous ethanol is 20-60 ml, the vigorous stirring time is 5-30 min, the heating temperature of the reactor is 100-240° C., and the insulation time is 5-12 h.
5. A photoelectrocatalyst Bi2S with sulfur / cobalt anion and cation double vacancies according to claim 1 3-δ / Co 1-x The preparation method of S is characterized by: The vacuum drying oven drying temperature in step (1), step (2) and step (3) is 30-150° C., and the insulation time is 6-16 hours; the centrifugal speed is 5000-12000 r / min, and the time is set to 1-6 minutes.
6. A photoelectrocatalyst Bi2S having sulfur / cobalt anion and cation double vacancies according to claim 1 3-δ / Co 1-x Photoelectrocatalyst Bi2S prepared by the preparation method of S 3-δ / Co 1-x S dual-function application, characterized by: Under visible light irradiation and a small applied bias, Bi2S 3-δ / Co 1-x S composite photoelectrocatalyst realizes the dual-functional application of catalytic hydrogen production and simultaneous degradation of organic pollutants.
Citation Information
Patent Citations
Bimetal sulfide nanoflower catalyst for degrading organic pollutants in water body and preparation method thereof
CN114345375A
Preparation method of double-vacancy cobalt nickel sulfide nanowire with electrochemical activity
CN116344230A